REHABILITASI SALURAN TERSIER DESA SUKOANYAR PAKIS KABUPATEN MALANG - Eko Noerhayati; Bambang Suprapto (Universitas Kadiri, 2020)
ABSTRACTThe rehabilitation channel carried out in Sukoanyar Village aims to improve the welfare of community empowerment and farmer development. Farmer's empowerment and development is improving tertiary irrigation network infrastructure, which increases yields. Proper irrigation channels can make irrigation water needs in the fields. This activity in 2020 collaboration with farmer groups and the City of Malang Public Works Water Resources Office. This activity is in partnership with the Sukoanyar Village Farmer Group, namely the Dewi Ratih I Farmer Group. According to the observation, he identified the problem Adalahn partners. In essence, the lack of some facilities in the tertiary irrigation network and absence management system is how to operate and maintain the tertiary canals. The solution offered is the repair facility on the channel. The repair is carried out infrastructure repairs of the irrigation network in the tertiary canal broke. The method of this activity is the community approach. The implementation stage is divided into three events, namely, planning, preparation, and execution of construction. At the end of the corresponding channel, activities resulted in the improvement of technical provisions so that the circuit can drain water into the fields correctly and impact on increasing yields. Keywords: Rehabilitation, irrigation, farming, tertiary ABSTRAKRehabilitasi saluran tersiar di Desa Sukoanyar bertujuan untuk meningkatkan kesejahteraan masyarakat desa melalui pemberdayaan dan pembinaan petani. Pemberdayaan dan pembinaan petani dilakukan melalui perbaikan sarana jaringan irigasi guna peningkatan hasil panen dengan cara efisiensi kebutuhan air irigasi teknis dengan perbaikan saluran tersier. Kegiatan ini dilakukan pada tahun 2020 bekerjasama dengan kelompok tani dan Dinas Pekerjaan Umum Sumber Daya Air Kabupaten Malang. Kegiatan ini dilakukan pada salah satu kelompok tani yang ada di desa Sukoanyar yaitu kelompok tani Dewi Ratih I. Berdasarkan pengamatan masalah mitra yang terindentifikasi pada survei antara lain: kurangnya beberapa sarana pada jaringan irigasi tersier dan kwarter yang vital, belum adanya sistem manajemen terutama penentuan pola tanam, kelembagaan kelompok tani yang masih lemah. Solusi yang ditawarkan adalah perbaikan fasilitas. Perbaikan-perbaikan tersebut adalah pada sub sistem pengadaan perbaikan sarana jaringan irigasi di saluran tersier yang sudah rusak. Metode pelaksanaan kegiatan ini dilakukan dengan pendekatan pada masyarakat. Tahap pelaksanaan dibagi menjadi 3 kegiatan yaitu perencanaan, persiapan dan pelaksanaan konstruksi. Pada akhir kegiatan dihasilkan saluran tersier yang telah diperbaiki sesuai dengan ketentuan teknis sehingga saluran dapat mengalirkan air ke sawah dengan baik yang berdampak pada peningkatan hasil panen. Kata kunci: Rehabilitasi, irigasi, tani, tersier